2008
DOI: 10.1002/jemt.20636
|View full text |Cite
|
Sign up to set email alerts
|

Types and numbers of sensilla on antennae and maxillary palps of small and large houseflies, Musca domestica (Diptera, Muscidae)

Abstract: Houseflies, Musca domestica, obtained from a high-larval-density culture were significantly (ca. 1.5 times) smaller than those from a low-larval-density culture. The same held true for their antennae and maxillary palps. Structure, number, and distribution of sensilla on antennae and palps of small and large flies were investigated using Scanning electron microscopy and Transmission electron microscopy. In each funiculus three pits were present, two (Type I) consisting of several compartments and one (Type II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
6
41
0
Order By: Relevance
“…cucurbitae, B. diaphora, B. dorsalis, B. minax, B. scutellata, and B. tau. The results in this study generally conform to those previously reported for other dipteran species (Sukontason et al 2003;Wasserman & Itagaki 2003;Spiegel et al 2005;Ngern-Klun et al 2007;Sukontason et al 2007;Chen & Fadamiro 2008;Smallegange et al 2008).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…cucurbitae, B. diaphora, B. dorsalis, B. minax, B. scutellata, and B. tau. The results in this study generally conform to those previously reported for other dipteran species (Sukontason et al 2003;Wasserman & Itagaki 2003;Spiegel et al 2005;Ngern-Klun et al 2007;Sukontason et al 2007;Chen & Fadamiro 2008;Smallegange et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…The MI are the most abundant on the maxillary palpi of both sexes of the 6 species. They were classified as non-innervated structures in some insect species (Fernandes et al 2002(Fernandes et al , 2004Sukontason et al 2007;Smallegange et al 2008). The microtrichia are most often described as mechanoreceptors associated with antennal structures (Hull & Cribb 1997;Siddiqui et al 2010), and specifically associated with dipteran antennae (Castrejon-Gomez & Rojas 2009; Arzuffi et al 2008;Chen & Fadamiro 2008;Fernandes et al 2002;Sukontason et al 2004Sukontason et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Female insects locate hosts by means of complicated behaviors in which sensilla play important sensing roles. For many insects, the antenna are important for olfaction, and sensilla distributed on the ovipositors are often used in oviposition behavior (Rice et al, 1973;Smallegange et al, 2008;Spänhoff et al, 2003a;Spiegel et al, 2005;Sukontason et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Trichoid sensilla, as one of the basic type of antennal sensilla in many other flies (Ross 1992;Shanbhag et al 1995;Hunter and Adserballe 1996;Shanbhag et al 2000;Sukontason et al 2004Sukontason et al , 2007Smallegange et al 2008;Liu et al 2013;Zhang et al 2013a, b), are undiscovered in R. purpureus. In some hippoboscids (Hippobosca equina, Hippobosca longipennis, Melophagus ovinus) (Zhang et al 2015) and phorids (Megaselia scalaris) (Loew) (Sukontason et al 2005), trichoid sensilla are also absent.…”
Section: Discussionmentioning
confidence: 98%
“…As the crucial sensory organs involved in feeding, mating, and spawning (Fernandes et al 2005;Amer and Mehlhorn 2006;Smallegange et al 2008;Guha et al 2012;Wang et al 2012), antennal sensilla of flies have managed to evolve various features to enhance their sensitivity and adaptability to the ever-changing environment (Ross 1992;Sukontason et al 2004;Zhang et al 2012aZhang et al , b, 2013aWang et al 2014). Little is known about the antennal sensilla of adult R. purpureus.…”
Section: Introductionmentioning
confidence: 96%